Advancing Islamic Education: Values-Driven Strategic Leadership in School Culture of the Digital Era - Jobeda Khanom; Mohamad Ali; Elias Ahmed (Walidem Institute and Publishing (WIP), 2025)
Objective: This research aims to explore the integration between strategic leadership, value-based management, and teacher development in improving the quality and sustainability of Islamic education in the digital age. The main focus is to design an educational model that aligns Islamic ethical principles with modern managerial and pedagogical approaches. Theoretical framework: This research is based on a combination of contemporary organizational leadership theory and classical Islamic educational philosophy, specifically the concepts of Tarbiyah (coaching), Ta'lim (teaching), and Ta'dib (formation of adab). This framework aims to connect Islamic ethics with the challenges of globalization, technology, and the demands of 21st-century society. Literature review: The literature review includes modern strategic leadership theories, the principles of traditional Islamic education, and previous research on institutional transformation in Islamic schools. In addition, an analysis of educational policies and managerial practices in Islamic institutions in Southeast Asia, the Middle East, and Muslim diaspora communities is also highlighted to reinforce contextual relevance. Methods: The research uses a qualitative approach with case studies on successful Islamic schools in various regions, complemented by a literature analysis and policy documents. The goal is to explore best practices in the transformation of Islamic values-based institutions. Results: Results show the importance of building spiritual leadership, integrating Islamic ethical values in institutional governance, digital-based and traditional-based teacher training, and ethical use of technology in Islamic education. Implications: This research provides a new direction for Islamic education reform to be more responsive to the digital age without abandoning spiritual values. These findings are useful for policymakers, educators, and managers of Islamic educational institutions. Novelty: The novelty of this study lies in the development of an integrative framework that integrates strategic leadership, Islamic ethics, and digital pedagogy, as well as presenting real-world examples of practice from various global contexts of Islamic education.